Electrically conducting films prepared from graphite and lignin in pure water - Suzuki, Asami; Otsuka, Yuichiro; Shikinaka, Kazuhiro (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, we present electrically conducting self-standing graphite films consisting of lignin derivatives extracted by simultaneous enzymatic saccharification and comminution (SESC). Sonication of graphite powder in the presence of SESC lignin and pure water allows dispersion of the SESC-lignin-attached graphite without addition of other chemicals. The SESC-lignin-attached graphite having a diameter of several micrometers can be used as a surface electroconductive coating and molded into self-standing films by drying. The SESC-lignin-attached graphite film exhibits higher conductivity (∼2,075 S/cm) than graphite-based composites consisting of ordinary lignin derivatives. Manufacturing self-standing films of micrometer-sized graphite using SESC lignin enables high electrical conductivity of the SESC-lignin-attached graphite film. The size of the SESC-lignin-attached graphite is proportional to the conductivity of the film. The SESC-lignin-attached graphite also acts as an antiplasticizer and a conductive filler for polymer films, i.e., conductive films consisting of poly(ethylene glycol) or Li+ montmorillonite can be obtained through a water-based process.